BIG DATA ANALYTICS METHODS USING GPU : A COMPREHENSIVE SURVEY (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Big data analytics is eventual discovery of knowledge from large set of data thus leading to business benefits. Its biggest challenge is the ability to provide information within reasonable time. The traditional analytics methods might fail to produce efficient result when data handled is of large size. As part of enhancing the performance, the researchers incorporated Graphical Processing Unit (GPU) on big data. GPU being the soul of computer delivers high performance by using its multi core parallel architecture. This paper investigates some methods of integrating GPU on analytics of big data that solely delivered high performance when compared to conventional schemes.